Drying of Highland Bamboo (Oldeania alpina) Culms Grown in Ethiopia as Quality Enhancement - Mahadi Mussa; Getachew Desalegn; Gemechu Kaba; Anteneh Tesfaye; Tsegaye Wubushet; Getachew Mezgebu (CV. Literasi Indonesia, 2023)
Drying is an essential step in the manufacturing process of bamboo culms which enhances its quality. Even though in the case of Ethiopia, effective bamboo culm drying has not been practiced. This is due to limited information/technology regarding bamboo culm drying. Therefore, this study aimed to investigate the effective drying technologies and the effect of site and culm height on the drying characteristics of Oldeania alpina (O. alpina). For this study, matured 3-5 years old samples of O. alpina culms sectioned into three segments were collected from Hagere-Selam and Rebu-Gebeya, Ethiopia. The culms were stacked and dried using kiln and air-drying methods. The mean values of basic density in O. alpina collected from Hagere-Selam and Rebu-Gebeya sites were 0.65 and 0.63 gcm-3, respectively. The average initial moisture content (MC) of Hagere-Selam and Rebu-Gebeya culms were 91.78% and 80.32%, respectively. The Hagere-Selam culm kiln-dried within 6.5 days while air-dried within 75 days to attain the final MC for kiln (10.15%) and air-drying (14.13%). The Rebu-Gebeya culm kiln dried within 5.4 days while they required 61 days for air-drying to attain the final MC for the kiln (10.60%) and air-drying (13.01%). The MC and drying time needed for drying the culms were significantly affected by site, culm height, and drying method. Drying O. alpina culms using kiln and air-drying methods was successful without significant drying defects. Well-seasoned culms of Hagere-Selam and Rebu-Gebeya are recommended for wider utilization in Ethiopia including furniture, flooring, handcrafts, etc.